Sisa pepejal dan pembersihan awam: pengurusan dan perundangan - Mohd Anuar, Haslinda; Abdul Wahab, Harlida (Perbadanan Pengurusan Sisa Pepejal Dan Pembersihan Awam (SWCorp), 2015)
Issues relating solid waste management are not a new issue in Malaysia. Starting with the jurisdiction given to the Local Authority, the jurisdiction to manage solid waste and public cleansing is now given to the Federal Government and implemented by the National Solid Waste Managenent Department, the Solid Waste and Public Cleansing Corporation and the contractors or licencees appointed.The takeover was meant to ensure the effectiveness of solid waste and public cleansing management thus reducing the environmental pollution caused by the weaknesses in the management and legislation. This article discusses two important aspects, that is, management and legislation of the solid waste and public cleansing by examining the provisions stated in the Solid Waste and Public Cleansing Management Act 2007.